Critical literacy: an approach to child rights education in Uganda and Canada - Shelley Jones; Kathleen Manion (Wiley, 2023)
For children to know how to fully participate in and most effectively lead the world they will inherit, they must learn how to critically engage with it and be knowledgeable about foundational rights and instruments that support such engagement. Together, critical literacy, which encourages the examination and interrogation of the underlying assumptions of dominant narratives and ‘legitimate’ knowledge, and children’s rights education, which involves children in learning how to express their ideas and fully participate in society (as appropriate to their age and ability), offer a powerful approach—theoretical and pedagogical—to engage children in active engagement of the world, especially with respect to the promotion of social justice. However, the layers of complexity and risks associated with deep consideration of challenging topics require expert guidance and compassionate role modelling from teachers of young children. Our paper considers the intersections between critical literacy and global child rights with reference to a study conducted with young school children in Canada and Uganda to discuss how teachers can support meaningful learning experiences in the classroom that can promote children’s agency and social justice commitments.
Keywords: critical literacy; child rights; Canada; Uganda; social justice; global education; participatory action research; multimodality; primary education; children’s rights